Territorial Citizenship in the Face of Hunger: The Role of Community Kitchens in the Agustibarrio Strategy of the El Agustino District, Lima Metropolitan Area, during the Covid-19 Pandemic - Alarcón Delgado, David (2024)
The article presents qualitative research on territorial citizenship in the neighborhoods of Santa Isabel and El Independiente, in the district of El Agustino, Lima. It analyzes how the Agustibarrio Strategy, specifically the actions of women in community kitchens, exemplify rooted territorial citizenship driven by local knowledge and collaboration among local actors. Furthermore, it highlights how their community participation becomes a form of resistance in the face of adversity, emphasizing the importance of social support networks in daily activities to combat hunger during the Covid-19 pandemic. The document is organized into five sections: an introduction where the objectives and conceptual framework that accompanies the research analysis are set out; a section that describes the methodology carried out; then the results and the analysis itself; and finally, the conclusions.